PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PEREDARAN JAJANAN ANAK SEKOLAH BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 dan UNDANG-UNDANG NOMOR 18 TAHUN 2012 (STUDI TERHADAP PERMEN JELI STIK TAHUN 2018 DI KENDAL) - A.M Tri Anggraini; Marcella Wanda Raditya (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
Technological advances have brought rapid and significant changes to the food industry. By using modern technology, the food industry is now able to produce on a very large scale including a variety of products with a very wide "range". Public consumption of imported and local food products tends to increase. Businessmen are aggressively encouraging consumers to consume excessively and often irrationally, so many incident that are suffered by consumers related to School Children Snack Food Like the incident that just happened in October 2018, namely poisoning cases of dozens of elementary school children in Kendal after consume stick shaped candy. In this paper the question is how the government controls the circulation of school children snacks, in this case BPOM for the 2018 Candy Jelly Candy case in Kendal and how legal protection for consumers for the circulation of snacks for school children. The method used by the author is a normative method. In its supervision of the School Children Snack Food, BPOM has taken steps in the task procedures and supervision functions. However, consumer cases occur related to School Children Food Snacks, actually caused by the three pillars of SisPOM that have not worked optimally. Business actors must comply with all procedures and conditions for distribution of processed food permits in accordance with existing regulations, BPOM must optimize its duties and functions as supervisors and consumers must always be smart and careful in choosing food products